Performance analysis of the T‐DOC® air‐charged catheters: An alternate technology for urodynamics. Issue 2 (17th July 2017) - Couri, Bruna M.; Bitzos, Stephanie; Bhardwaj, Deepak; Lockhart, Emily; Yue, Andy; Goping, Ing
Abstract : Aims: Urodynamics (UDS) is widely used for the diagnosis of lower urinary tract dysfunction. Air‐Charged catheters (ACC), one of the newer technologies for UDS pressure recording, has been adopted in growing numbers around the world for the past 15 years. Currently, there is a lack of published studies characterizing specific performance of the ACC. Since linearity, hysteresis, pressure drift, and frequency response are important components in characterizing accuracy for catheter‐manometer systems; this study aimed to assess these four aspects in ACC. Methods: A total of 180 T‐DOC® ACC were used in three different laboratory settings to assess pressure linearity and hysteresis (15 dual‐sensor vesical and urethral and 30 single‐sensor abdominal), pressure drift over 2 h (115 single‐sensor), and frequency response (20 single‐sensor). Data are presented as mean ± standard deviation. Results: ACC showed linearity of 0.99 ± 0.01, 0.99 ± 0.01, and 1.01 ± 0.01; and hysteresis of 0.57 ± 0.3%, 0.76 ± 0.48%, and 1 ± 0.89% for the abdominal, vesical, and urethral sensors, respectively. A pressure drift of 2.2 ± 1.4% at 1 h and 4.4 ± 2.5% at 2 h were observed when compared to baseline pressures. The catheters did not show any amplification factor during the sweep from 1 to 30 Hz, and recorded signals up to 5 Hz attenuating higher frequency signals. Conclusions: In this study the T‐DOC® ACC showed a linear performance with minimal hysteresis associated with acceptable pressure drift, and adequate frequency response to capture clinically relevant pressures. The accurate results observed in this study suggest that these catheters are technically suitable to be used as a measuring instrument for UDS.